Teachers’ opinions on heterogeneous classes: Insights for EFL teacher education - (:unkn) unknown (Springer Science and Business Media Deutschland GmbH, 2021)
Heterogeneous classes are those that are composed of different types of learners. Classrooms throughout the world are becoming more and more diverse, which inevitably impacts the learning and teaching process. The aim of the study presented in this chapter was to explore how pre-service and in-service EFL teachers perceived the issue of heterogeneity, and to report the benefits and challenges of heterogeneous classes as perceived by them. The study included two groups of participants from Turkey: 61 pre-service teachers in their 3rd year of study in the ELT program, and 14 in-service teachers of English as a foreign language. As part of the data collection procedure, the participants were given open-ended questions to elicit their views and perceptions, which were then qualitatively analyzed. Results indicate that for both pre- and in-service participants, there is a need for a more broadened view and greater awareness of diversity. The advantages of heterogeneity for pre-service teachers centered around exposure to diversity and tolerance, and for in-service teachers the exchange of information and cooperation among learners. The challenges of heterogeneous classes most frequently cited by both groups of teachers were: less successful students feeling neglected, high achieving students getting bored, and instructors struggling to meet the needs of all learners. The stated challenges indicate that more information and practice on how to teach diverse learners with varying backgrounds need to be provided to teachers. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2021.
Keywords: EFL; Heterogeneity; In-service teachers; Language teacher education; Pre-service teachers